2001
DOI: 10.1038/sj.ijo.0801633
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ten year body weight variability on cardiovascular risk factors in Japanese middle-aged men and women

Abstract: OBJECTIVE:The purpose of the present study was to determine the effects of weight variability on cardiovascular risk factors (CRF) based on a large sample of community-resident Japanese males and females. METHOD: A total of 3564 men and 1955 women, all Japanese, aged 30±69 y in the baseline year (1987), were followed-up for up to 10 y (end-point in 1996). Height, body weight, systolic and diastolic blood pressure, fasting serum total cholesterol, triglyceride and fasting plasma glucose were measured as an annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 17 publications
6
38
0
1
Order By: Relevance
“…22 When analyzing individual parameters or clusters taking the confounders into account, our results are in accordance with worldwide previous studies showing associations of blood pressure and lipid profile changes over time with changes in BMI for both sexes. 4,6,8,23,24 In addition, similarly to previous investigations, changes in GGT activity and uric acid concentrations 15 were significantly associated with BMI gain in both genders and no association was found with changes in fasting blood glucose levels. 4,7 Conversely, BMI changes were associated with changes in ALP and in inflammatory markers (hs-CRP, haptoglobin, orosomucoid and summary cluster inflammation) in women only.…”
Section: Discussionsupporting
confidence: 82%
“…22 When analyzing individual parameters or clusters taking the confounders into account, our results are in accordance with worldwide previous studies showing associations of blood pressure and lipid profile changes over time with changes in BMI for both sexes. 4,6,8,23,24 In addition, similarly to previous investigations, changes in GGT activity and uric acid concentrations 15 were significantly associated with BMI gain in both genders and no association was found with changes in fasting blood glucose levels. 4,7 Conversely, BMI changes were associated with changes in ALP and in inflammatory markers (hs-CRP, haptoglobin, orosomucoid and summary cluster inflammation) in women only.…”
Section: Discussionsupporting
confidence: 82%
“…[18][19][20][21][22] However, recent studies discuss the weak adverse effects of weight cycling on cardiovascular risk factors. 23,24 Several reviews remark that these studies have some limitations and that information about the causes of the weight change is missing. 18,25 It has been suggested that the adverse effects of weight cycling could be due to a redistribution of body fat to the upper body compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with other studies, we found no interaction between WF and weight change on the risk for MS or each MS component. 10,[31][32][33] There are a number of previous studies that have investigated the relationships between WF and each individual component of the MS. 10,[31][32][33][34][35][36][37] In our study, we found that WF had an increased risk for BP, HDL-c and WC. ORs for the fasting blood glucose and TG components followed the same trend and we assume that their nonsignificant results were related to insufficient statistical power (the number of cases was smaller than those for other components).…”
Section: Discussionmentioning
confidence: 99%
“…35 However, other studies did not support the hypothesis that WF have deleterious effect on these CVD risk factors. 10,[31][32][33]37 These contradictions could be attributed to the different methods used for estimating WF. There is no single definition of weight cycling which makes comparisons between studies difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation